A Citizen’s Democracy in Authoritarian Times: An American View on the Catalan Drive for Independence (2018)
Agents of sedition who are heedlessly destroying Spain’s “consolidated democracy”? Xenophobes simply interested in protecting their own wealth who are, behind the rhetoric, not that different from the tribal authoritarians coming to the fore in Hungary and northern Italy? These are but two of the many narrative tropes the Spanish government and the establishment press in Europe and the US are rolling out to counter the rise of separatist sentiment in Catalonia. In this book, Thomas S. Harrington, an American with a deep familiarity with Catalan culture and history, argues that, far from being a threat to democracy in Europe, the scrupulously peaceful and people-driven movement for independence in Catalonia is, perhaps, the best hope we have for spurring its much hoped-for renewal.Hi ha agents de sedició que estan destruint sense consciència la “democràcia consolidada” d’Espanya? Xenòfobs interessats només a protegir la seua riquesa que, més enllà de la retòrica, no són tan diferents dels autoritaris tribals que han sorgit a Hongria i el nord d’Itàlia? Aquests són només dos dels molts trops narratius que el govern espanyol i la premsa del “establishment” a Europa i els EUA estan desplegant per a contrarestar l’augment del sentiment separatista a Catalunya. En aquest llibre, Thomas S. Harrington, un nord-americà amb un profund coneixement de la cultura i la història catalanes, argumenta que, lluny de ser una amenaça per a la democràcia a Europa, el moviment independentista, escrupolosament pacífic i impulsat pel poble, a Catalunya és, potser, la millor esperança que tenim per a impulsar-ne la tan esperada renovació.
Keywords: Politics; Culture; media; perception managment; Catalonia; Spain; Nationalism; Iberian culture; European politics; Independence movements; EU; repression; Democracy; authoritarianism; Spanish Transition; Catalan History; Historycitizenship